PERBANDINGAN KARAKTERISTIK DONAT DENGAN PENAMBAHAN TEPUNG TULANG IKAN: The comparison of the Characteristics of Donuts with the Addition of Fishbone Flour - Nike Poppy Purwatti; Elly Masliha; Listiana Pratiwi; Iffah Muflihati; Sari Suhendriani; Rizky Muliani Dwi Ujianti (Universitas Darussalam Gontor, 2022)
Fish bones can be processed into flour and applied to food products due to their high nutritional content and can be used in food. Diversification is done through the use of fish bone flour on donuts. The purpose of this study was to compare the characteristics of donuts added with various types of fish bone flour. The experimental design used was a completely randomized design (CRD) with 3 different types of fish bone flour: catfish bone flour, milkfish bone flour, and tuna fish bone flour. The analysis carried out in this study was the analysis of water content, ash content, color, swellability, and organoleptic (descriptive and hedonic tests). The results of color analysis showed that the color of the donut closest to the control was the donut with the addition of catfish bone flour. Donuts with the addition of catfish bone flour had the swellability value that was closest to the control. The water content of the donut with the addition of tuna bone flour produced has a water content value that is closest to the control. The value of the ash content of the donut that is closest to the control is the value of the ash content of the donut with the addition of milkfish bone flour. The results of the descriptive test showed that the order closest to the control was donuts with the addition of catfish bone flour, donuts with the addition of milkfish bone flour and donuts with the addition of tuna fish bone flour. The hedonic test showed that the most preferred donuts by the panelists were donuts with the addition of catfish bone flour.